Successful Reconstruction of Extensive Skin Defect by Skin Flap Technique Post Excision of Perineal Adenocarcinoma - V. Bhuvaneshwari; D. Jenita Rani; M. Madeena Begum (The Indian Veterinary Journal, 2023)
An eleven year old intact male Spitz cross dog was brought to the hospital, with a history of tumour in the perineal region for the past six months. Physical examination revealed a huge tumour mass with multiple ulcerations were noticed on the left side of the perineal region. On clinical examination all the vital parameters were under normal range. The condition was diagnosed as perianal tumour and surgery was fixed for tumour excision and skin defect reconstruction. Pre-operative blood was collected for hemato-biochemical analysis. Thoracic and abdominal radiograph was taken to rule out metastasis. Under general anaesthesia, tumour excision was done with 4 cm healthy margin and the skin defect in the operated site was reconstructed with the help of skin flap technique. Post-operative care with antibiotic, analgesic and wound dressing continued for seven days. The sutures were removed on 10th post-operative day and the animal made an uneventful recovery.